(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
this article covers the theoretical sources of scientists who have brogan research on how the development of reflexive competence, which occurs in adolescence, manifests itself in adolescence and the achamite of one’s own self, buy onalish.